Latin America at the end of politics - Colburn, Forrest D. (Princeton University Press, 2002)
After decades of ideological struggle, much of it in the service of an elusive socialist ideal, Latin America has embraced liberalism--democracy and unfettered markets. But liberalism has triumphed more by default than through exuberance. The region's democracies are fragile and lethargic. Despite pronounced social inequality, widespread poverty, and other difficulties, the populace is not engaged in deep discussions about state and society. The end of ideological contests has dampened political conflict, but likewise lessened the sense of urgency for solving trenchant problems. Political fatigue and devotion to acquisition have smothered egalitarianism as even an ideal. There is an uneasy social indifference. Latin America at the End of Politics explores this period of circumscribed political passions through deft portrayals of crucial political, economic, social, and cultural issues: governance, entrepreneurs and markets, urban bias, poverty, the struggle for women's equality, consumerism, crime, environmental degradation, art, and migration of the poor. Discussions of these issues are enriched by the poignant narratives of emblematic individuals, many of whom are disoriented by the ideological void of the era.